The complete mitochondrial genome of Pink warty sea cucumber (Cercodemas anceps Selenka, 1867). Issue 3 (4th March 2021) - Li, Huo; Liu, Jinshang; Wang, Shengpeng; Huang, Wen
Abstract: In this study, we sequenced the circular mitochondrial genome (mitogenome) of Cercodemas anceps . This genome was determined to measure 16, 539 bp in length and contain 13 protein-coding genes (PCGs), 22 tRNA genes, and 2 rRNA genes. The longest gene was observed to be nad5, which measures 1, 641 bp in length and is located at position 6, 540 ∼ 8, 180 of the C. anceps mitogenome. One PCG, nad6, and five tRNA genes ( tRNA Ser(UCN), tRNA Gln, tRNA Ala, tRNA Val, and tRNA Asp ) were located on the light chain, and the other genes were located on the heavy chain. A phylogenetic tree was constructed with the mitogenome sequences of 26 types of echinoderm species, and the results show that C. anceps is most closely related to C. quadrangularis .